2017
DOI: 10.1021/acsbiomaterials.7b00069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Multicellular Tumor Spheroid Formation Methods and Implications for Drug Screening

Abstract: Improved in vitro models are needed to better understand cancer progression and bridge the gap between in vitro proof-of-concept studies, in vivo validation, and clinical application. Multicellular tumor spheroids (MCTS) are a popular method for three-dimensional (3D) cell culture, because they capture some aspects of the dimensionality, cell–cell contact, and cell–matrix interactions seen in vivo. Many approaches exist to create MCTS from cell lines, and they have been used to study tumor cell invasion, growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 68 publications
6
75
0
2
Order By: Relevance
“…In our experiments, cells seeded onto 2D biomaterials or as single cells in 3D resided in those environments for 24 hours, so they likely relied exclusively on the provided collagen I (2D) or RGD (3D) for integrin-mediated signaling. However, breast cancer cells grown as spheroids upregulate ECM genes, such as fibronectin, suggesting additional ECM proteins, not provided by us initially, contribute to the observed cell response 20 . Recent work has shown that the ECM-mediated signaling can impart resistance to combined inhibition of PI3K and HER2 34 , but our method identified that targeting two nodes in the same pathway, Raf with sorafenib and MEK with PD0325901, is a promising combination therapy for breast cancer.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In our experiments, cells seeded onto 2D biomaterials or as single cells in 3D resided in those environments for 24 hours, so they likely relied exclusively on the provided collagen I (2D) or RGD (3D) for integrin-mediated signaling. However, breast cancer cells grown as spheroids upregulate ECM genes, such as fibronectin, suggesting additional ECM proteins, not provided by us initially, contribute to the observed cell response 20 . Recent work has shown that the ECM-mediated signaling can impart resistance to combined inhibition of PI3K and HER2 34 , but our method identified that targeting two nodes in the same pathway, Raf with sorafenib and MEK with PD0325901, is a promising combination therapy for breast cancer.…”
Section: Discussionmentioning
confidence: 70%
“…To create tumor spheroids, single cells were encapsulated sparsely in polyNIPAAM hydrogels and grown into uniform clonal spheroids over 14 days in culture (Figure 1b–d). This 14 day endpoint achieves a relatively homogeneous population of viable multicellular tumor spheroids with an average diameter less than 100 µm (Figure 1b–c) 20 . This diameter was chosen to ensure drug 21 and oxygen diffusion into the spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, cells seeded onto 2D biomaterials or as single cells in 3D only resided in that platform for 24 hours, so they likely relied exclusively on the provided collagen I (2D) or RGD (3D) for biochemical signals. However, breast cancer cells grown as spheroids upregulate ECM genes, such as fibronectin, suggesting additional ECM cues might contribute to resistance 20 . Recent work has shown that the ECMmediated signaling can impart resistance to combined inhibition of PI3K and HER2 32 , but our method identified that targeting two nodes in the same pathway, Raf with sorafenib and MEK with PD0325901, is a promising combination therapy for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed a system to independently evaluate the effects of both the geometry and stiffness of the microenvironment on breast cancer cell response to targeted and non-targeted drugs. We measured the GR 50 (concentration of drug which dampens growth by 50%) 15 20 . This diameter was chosen to ensure drug 21 and oxygen diffusion into the spheroids.…”
Section: Geometry Impacts Innate Breast Cancer Cell Response To Rtk/mmentioning
confidence: 99%
“…To achieve these goals, conventional two dimensional (2D) cell culture devices are insufficient, while animal studies may impose additional challenges regarding mechanistic understanding of the complex cell-matrix and cell-cell interactions, as well as the physical alterations that occur in the PDAC TME (Figure 1). As such, extracellular matrix (ECM)-derived and synthetic polymer-based three-dimensional (3D) hydrogels (Table 1) are increasingly developed and used for understanding the influences of microenvironment cues on cancer progression [3035]. While the use of 3D matrices for PDAC research is in early stage, great strides have been made in recent years (Table 2).…”
Section: Tumor Microenvironment In Pdacmentioning
confidence: 99%